Analysis of changes in soil chemical stoichiometric ratios under different cultivation durations of Pennisetum giganteum in inner Mongolia, China - Shao, Yazhou; Ma, Yunxia; Li, Gangtie; Ma, Xiaolu (Frontiers in Environmental Science, 2025)
This study aims to investigate the impact of Pennisetum giganteum cultivation on soil stoichiometric ratios in different regions of Inner Mongolia (Naiman Banner, Ulan Buh Desert, and Tumd Left Banner), clarifying the relationship between years of cultivation and changes in soil nutrient contents as well as stoichiometric ratios, thereby providing a scientific basis for regional ecological restoration. The experimental design used Pennisetum giganteum as the research subject, establishing experimental plots in three regions. Soil samples from 0 to 100 cm at different depths were collected before planting (CK), after the first-year harvest (YK), and after the second-year harvest (EK). The contents of soil SOC, TN, and TP were measured, and the ratios of C/N, C/P, and N/P were calculated. Through one-way ANOVA and Pearson correlation analysis, the relationships among cultivation years, soil depth, and soil nutrients as well as stoichiometric ratios were evaluated. The results indicate that Pennisetum giganteum cultivation significantly increased soil nutrient contents. For example, in Naiman Banner, the soil layer of 0–10 cm showed an increase in C from 1.41 g/kg to 2.06 g/kg, N from 1.47 g/kg to 1.74 g/kg, and P from 1.27 g/kg to 1.85 g/kg. Changes in soil stoichiometric ratios varied with region and soil depth: in Tumd Left Banner, the C/N ratio generally decreased (e.g., from 1.48 to 0.77 in the 0–10 cm soil layer), indicating an accelerated rate of N accumulation; whereas in the Ulan Buh Desert, the C/N ratio exhibited an increasing trend, possibly due to more pronounced C accumulation under arid conditions. The C/P and N/P ratios decreased in most regions, reflecting an improvement in P availability. Correlation analysis revealed that cultivation years were significantly positively correlated with soil C, N, and P contents, while they were mostly negatively correlated with the C/P and N/P ratios.